1980
DOI: 10.1002/jso.2930150402
|View full text |Cite
|
Sign up to set email alerts
|

The immune response to prostate cancer: An evaluation and a review

Abstract: The effects of stage and therapy of prostate cancer on the immune response were evaluated in 193 patients with an histologic diagnosis of prostatic malignancy. There was little or no effect, as measured by these generally non-specific tests, on the immune response. The host-tumor immune interaction is difficult to evaluate in prostate cancer. The complexities of measuring prostate tumor immunity are discussed and the literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, Smith initially reported that the prostate gland is devoid of afferent lymphatics [4]. Moreover, non-specific tests of immune function, such as T cell rosette formation, T cell blastogenic response to mitogen stimulation, and DTH responses to common recall antigens, were all found to be reduced in patients with prostate cancer [5,6]. Other studies documented the reduction of MHC class I molecules in metastatic prostate cancer lesions, the disruption of the TAP transporter machinery in human prostate cancer cell lines, and the overexpression of TGF␤ by prostate cancer cells as multiple possible mechanisms of prostate cancer escape from immune detection [7].…”
Section: Background and Overviewmentioning
confidence: 99%
“…For example, Smith initially reported that the prostate gland is devoid of afferent lymphatics [4]. Moreover, non-specific tests of immune function, such as T cell rosette formation, T cell blastogenic response to mitogen stimulation, and DTH responses to common recall antigens, were all found to be reduced in patients with prostate cancer [5,6]. Other studies documented the reduction of MHC class I molecules in metastatic prostate cancer lesions, the disruption of the TAP transporter machinery in human prostate cancer cell lines, and the overexpression of TGF␤ by prostate cancer cells as multiple possible mechanisms of prostate cancer escape from immune detection [7].…”
Section: Background and Overviewmentioning
confidence: 99%